Leadership and Post-Conflict State Rebuilding: Iraq after 2003: Case Study - Ali, Inass Abdulsada; Qati, Sana Kadhim; Alwan, Batool Husain (Journal of Humanities & Social Sciences, 2020)
The Iraqi political and social arena was characterized, subjectively and objectively, by the weakness of leadership building. This has led to a leadership crisis, reflected in the outcome of the quality of the process of rebuilding the state in Iraq. Thus, this building process lacked the simplest requirements and conditions of success. It also suffered from a major and obvious failure, the leadership crisis was one of its causes, as the situation in Iraq has raised conflict leaders, not building leaders, and this confirms the existence of a cultural crisis in the production of conscious, aware leadership and compatible with democratic action. Using the methodology of moving from general to private, based on descriptive and analytical approaches, the paper considered studying the themes of the research, leadership - state building - the role of leadership in state-building, separately and linking each theme at the end of it to the Iraqi context. The weakness of the leadership in Iraq is reflected in a series of sustainable crises that are in need of radical solutions, in accordance with long-term strategic plans, especially in the absence of building visions and predominance of self-interest, along with the impact of social reality on leadership practices, which had an impact on the state-building.